2021
DOI: 10.1002/cbin.11704
|View full text |Cite
|
Sign up to set email alerts
|

The roles, controversies, and combination therapies of autophagy in lung cancer

Abstract: Lung cancer is one of the leading causes of death among men and women worldwide. The disease initially has a silent phenotype, which leads to the progression of the disease and ultimately the lack of proper response to routine treatments. Autophagy, known as an intracellular “recycle bin” for the degradation of defective proteins and molecules, is one of the mechanisms that has been considered in the context of cancer in recent years. This study aims to provide a comprehensive review of published articles on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…In recent years, modulating autophagy has been proposed as a promising treatment for lung cancer, as it plays a central role in tumorigenesis and tumor progression ( Nam, 2021 ; Wang et al, 2022 ). Autophagy seems to be a double-edge sword, as it can play both cytoprotective and cytotoxic roles in cells, in a context-specific way ( Colhado Rodrigues et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, modulating autophagy has been proposed as a promising treatment for lung cancer, as it plays a central role in tumorigenesis and tumor progression ( Nam, 2021 ; Wang et al, 2022 ). Autophagy seems to be a double-edge sword, as it can play both cytoprotective and cytotoxic roles in cells, in a context-specific way ( Colhado Rodrigues et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the early stages of cancer development, autophagy is believed to protect the cells against cancer initiation. Once a tumor is established, the neighboring microenvironment is often hypoxic and nutrient-deprived, and autophagy fuels and supports cancer cells growth, switching into a tumor promoter role ( Wang et al, 2022 ). Autophagy also promotes epithelial–mesenchymal transition, migration, and invasion of tumoral cells ( Li et al, 2013 ; Zhu et al, 2014 ; Luo et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is an intracellular degradation and recycling mechanism that helps cells cope with various environmental stresses and, to some extent, participates in the regulation of cell death. During chemotherapy and radiotherapy, lung cancer cells often employ autophagy as a mechanism to mitigate intracellular damage and stress, thereby enhancing cell survival and evading therapeutic effects ( Guo et al, 2022 ; Wang et al, 2022 ). Research has demonstrated that lung cancer cells exhibit heightened autophagic activity after prolonged chemotherapy or targeted treatment, resulting in the degradation of drug target proteins and repair-capable proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, mitochondria were corroborated to promote aerobic oxidation for lung cancer survival and metastasis ( Li F. et al, 2020 ; Sorrenti et al, 2021 ). The latest review also shows that the combination of traditional therapies and autophagy inhibitors including 3-MA can improve the efficacy of lung cancer ( Wang Z. et al, 2021 ), and even intervention in specific autophagy genes can improve the response rate of immunotherapy ( Lawson et al, 2020 ). We have revealed that YFSJ-treated patients express higher microRNA-182 than those in the control group, and microRNA-182 was predicted and verified to target Atg7 (data not shown).…”
Section: Discussionmentioning
confidence: 99%